Oasis of Tourism in the Middle of Palm Plantations: The Survival Strategy of Small Farmers "Pusaka Tani Sidomulyo" - Humaira; Maulana Rizky Wijaya; Diana Santi; Syauqiy Ridlo Robbiy (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2023)
Farmers in developed and some developing countries have good financial stability. The size of the cultivated area is the key to the level of welfare of farmers, the more land that is managed, the greater income that will be obtained. In the end, it can provide Economic stability for the farmers themselves. On the other hand, 41% of farmers in developing countries can be categorized as small farmers who do not have enough income. Smallholder farmers here can be categorized as farmers with a cultivated area of approximately 1 hectare of land. In fact, FAO as a high-ranking organization that concentrates on agriculture and plantations states "small farmers need other side jobs to make ends meet". The above facts show the need for intervention from various parties in helping small farmers, especially in dealing with these problems. One of the community empowerment programs carried out by PT Pertagas OSSA is to keep small farmers alive with agricultural and plantation fields and businesses through social safety nets by creating other business units. Some of the business units that are used as social safety nets are:  1) utilization of empty bunch waste into mushroom growing media and organic fertilizer, 2) empowerment of women in productive Economic fields, 3) encouraging the creation of Eco edu tourism, 4) utilization and management of resources to meet basic water needs, and 5) utilization and management of infrastructure resources such as fishing ponds, swimming pools, selfie locations as tourist destinations in the middle of the plantation.